Identification Public Space of Sport in Pesawaran Regency - Candra Kurniawan; Hari Setijono; Taufiq Hidayah; Hadi Hadi; Sugiharto Sugiharto; Heru Sulistianta (Universitas Negeri Semarang, 2021)
The public space of sport development index is a value that reflects the success of sports development based on the dimensions of public space available for the community to exercise regularly and supports the level of physical fitness of the community. This study aimed to analyze the dimensions of the development of public sports spaces in Pesawaran Regency, Lampung Province. This study uses quantitative methods with an evaluation analysis approach that refers to the indicators of the public space index of sport development. The study results: The data from the index of the public sports space in the Pesawaran Regency is 0.271. Conclusion: The public space of sport index is still in the low category, and there is a need for a local government support program to pay attention to and improve sustainable sports development.